2016
DOI: 10.1093/sysbio/syw039
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Stratigraphic Congruence Across Trees, Higher Taxa, and Time

Abstract: The congruence between the order of cladistic branching and the first appearance dates of fossil lineages can be quantified using a variety of indices. Good matching is a prerequisite for the accurate time calibration of trees, while the distribution of congruence indices across large samples of cladograms has underpinned claims about temporal and taxonomic patterns of completeness in the fossil record. The most widely used stratigraphic congruence indices are the stratigraphic consistency index (SCI), the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 147 publications
2
14
0
Order By: Relevance
“…Many studies contrast the stratigraphic gaps implicit to inferred phylogenies from different taxa or intervals of time (e.g., Benton and Storrs 1994; Hitchin and Benton 1997; Wills 1999, 2007; Benton et al 2000; O'Connor et al 2011). O'Connor and Wills (2016) assess a variety of reasons why differences might exist other than sampling, although they do not include differences in diversification rates. Bapst (2013) shows that differences in diversification offer another reason why two clades with otherwise similar preservation potential will have phylogenies with different summed branch durations and thus stratigraphic gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies contrast the stratigraphic gaps implicit to inferred phylogenies from different taxa or intervals of time (e.g., Benton and Storrs 1994; Hitchin and Benton 1997; Wills 1999, 2007; Benton et al 2000; O'Connor et al 2011). O'Connor and Wills (2016) assess a variety of reasons why differences might exist other than sampling, although they do not include differences in diversification rates. Bapst (2013) shows that differences in diversification offer another reason why two clades with otherwise similar preservation potential will have phylogenies with different summed branch durations and thus stratigraphic gaps.…”
Section: Discussionmentioning
confidence: 99%
“…These sites are critically important for the arthropod fossil record because of their relatively low preservation potential of many groups, as is particularly the case for terrestrial arthropods, being less well mineralised than many of the marine groups. This is reflected in the low level of congruence between the order of appearance of lineages in the fossil record (stratigraphic appearance) and the order of phylogenetic branching (Wills, 2001;O'Connor and Wills, 2016) in arthropods, as compared to more congruent datasets such as tetrapods (Benton et al, 1999(Benton et al, , 2000Norell and Novacek, 1992). Clustering of calibrations at Konservat-Lagerstätten localities may lead to highly variable lengths of ghost lineages for the different taxa that are preserved together at these sites, and indeed many of the clades in our database have soft maxima that are substantially older than their hard minimum date.…”
Section: Discussionmentioning
confidence: 99%
“…The high SCI and GER values of cynodonts contrast with their low MSM* values (22%). It has been observed that tetrapods in general have a lower MSM* (<50%) than plants, fishes or echinoderms, but higher than arthropods and molluscs (O'Connor & Wills 2016). MSM* has been found to be heavily biased by tree size and shape (Siddall 1998), more so than SCI and GER, and it does not correlate strongly with other metrics (O'Connor & Wills 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that tetrapods in general have a lower MSM* (<50%) than plants, fishes or echinoderms, but higher than arthropods and molluscs (O'Connor & Wills 2016). MSM* has been found to be heavily biased by tree size and shape (Siddall 1998), more so than SCI and GER, and it does not correlate strongly with other metrics (O'Connor & Wills 2016). Furthermore, MSM* is negatively correlated with the number of taxa included within the tree (O'Connor & Wills 2016), which might explain why the value for cynodonts is low given the relatively high number of taxa used here.…”
Section: Discussionmentioning
confidence: 99%